2018
DOI: 10.5194/acp-18-5045-2018
|View full text |Cite
|
Sign up to set email alerts
|

Continuous non-marine inputs of per- and polyfluoroalkyl substances to the High Arctic: a multi-decadal temporal record

Abstract: Abstract. Perfluoroalkyl acids (PFAAs) are persistent, in some cases, bioaccumulative compounds found ubiquitously within the environment. They can be formed from the atmospheric oxidation of volatile precursor compounds and undergo long-range transport (LRT) through the atmosphere and ocean to remote locations. Ice caps preserve a temporal record of PFAA deposition making them useful in studying the atmospheric trends in LRT of PFAAs in polar or mountainous regions, as well as in understanding major pollutant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 81 publications
8
60
0
Order By: Relevance
“…Fluorotelomer degradation leads to deposited PFCAs with ratios that are reasonably consistent with time. Pickard et al (2018) observed that all PFCAs with carbon chain lengths ≥5 have similar deposition trends through time to the same Devon Ice Cap ice core. Ratios among PFCAs with five to eight carbons are reproduced in Figure 2b and demonstrate the difference in deposition trends for PFBA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorotelomer degradation leads to deposited PFCAs with ratios that are reasonably consistent with time. Pickard et al (2018) observed that all PFCAs with carbon chain lengths ≥5 have similar deposition trends through time to the same Devon Ice Cap ice core. Ratios among PFCAs with five to eight carbons are reproduced in Figure 2b and demonstrate the difference in deposition trends for PFBA.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Comparison between GEOS‐Chem modeled (Thackray et al, 2020) and measured deposition ranges from 1978–2014 (Devon Ice Cap, black) and 1978–2015 (Mt. Oxford icefield, green); (b) measured molar ratios of PFCAs of different chain lengths from the Devon Ice Cap (C5 to C8 PFCA deposition from Pickard et al (2018)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, the PFAS issue became very public when residents near DuPont‘s Washington, West Virginia manufacturing site filed a class action law suit due to the elevated PFOA levels in their drinking water (Frisbee et al., 2009; Head, 2019; Steenland et al., 2009). About the same time, the international community became alarmed to find that PFAS were not only commonly found in human serum but were also detected in wildlife, including wildlife found in the arctic and other remote areas (Del Vento et al., 2012; Giesy & Kannan, 2001; Hepburn et al., 2019; Lindstrom et al., 2011; MacManus‐Spencer et al., 2010; Perez et al., 2013; Pickard et al., 2018; Taves, 1968). The PFAS most commonly detected in the environment were long chain (C8) “legacy” chemicals, PFOA and PFOS.…”
Section: Pfas Historymentioning
confidence: 99%
“…The use of tainted recycled fiber or the use of tainted water for composting operations could account for the banned PFAS detected. It is also possible that some noncompliant food packaging entered the market via importation (Choi et al., 2019; Pickard et al., 2018).…”
Section: Pfas Uses In Food Packagingmentioning
confidence: 99%